(-)-Calcaridine B, a new chiral aminoimidazole-containing alkaloid from the marine sponge Leucetta chagosensis. Issue 11 (2nd November 2019) - Tang, Wei-Zhuo; Yang, Zhong-Zhen; Sun, Fan; Wang, Shu-Ping; Yang, Fan; Jiao, Wei-Hua; Lin, Hou-Wen
Abstract: LC-DAD/MS-based dereplication of organic extract of a calcareous sponge Leucetta chagosensis afforded one new chiral aminoimidazole-containing alkaloid, (-)-calcaridine B (1 ), along with one achiral imidazole analog leucettamine E (2 ) as well as one known imidazole derivative (2 E, 9 E )-pyronaamidine-9-( N -methylimine) (3 ). Their structures were elucidated on the basis of NMR spectroscopic analyses, and comparing with the literature. The cytotoxic activities of all isolates were evaluated against three human cancer cell lines, and compounds 1 and 3 exhibited mild cytotoxicities toward the MCF-7 cell line with IC50 values of 25.3–24.2  μ M, respectively. Graphical Abstract: